WATER-SOLUBLE ORGANIC-CONSTITUENTS IN ARCTIC AEROSOLS AND SNOW PACK - Li, S. M.; WINCHESTER, JW (GEOPHYSICAL RESEARCH LETTERS, 1993)
Eight water-soluble organic anions were measured in 70 aerosol samples and 10 snow samples at Barrow, Alaska in March-April, 1989. The ranking of the ions in aerosols according to total (coarse+fine aerosol) median concentrations was acetate (44 ng m-3), oxalate (27), benzoate (23), formate (22), propionate (6), methanesulfonate (5), lactate (4), and pyruvate (4). When added up, the median organic anion mass was 156 ng m-3. The organic anions/nssSO4= mass ratio had a median of 0.18 and 0.07 in the coarse (>l mum) and fine (<1 mum) size fractions, respectively, but can be very high on occasions. On average, the organic anions made up more than 10% of the water-soluble aerosol mass. A similar ranking in concentration was also found for the organic ions in the snow pack samples. The organic anion/nssSO4= mass ratio in these samples was >0.5, substantially higher than in aerosols.